2020
DOI: 10.13106/jafeb.2020.vol7.n10.823
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Service Quality on Bank Customers’ Satisfaction in Bangladesh

Abstract: In this competitive era, it has become a prerequisite for the financial firms providing banking services to understand and meet the customers' needs and demands to remain competitive in today's market environment. Without satisfying the customers, banking business cannot stand alone. To satisfy customers, it is often recommended to provide better quality banking services to the bank customers. Providing quality banking services has become a prime strategic tool for the banking sector nowadays. Therefore, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
1
12
0
6
Order By: Relevance
“…Among these variables, Equity to Asset Ratio (EAR) and Deposit to Asset ratio (DTAR) are statistically significant [30,31] at 1% level of significance on ROA-and have significant impact of GDPGR-Gross Domestic Product Growth Rate on ROA-Return on Asset at 5% level of significance. Several researchers [8,12,15] found same type of findings. Tan and Floros [36], Ariyadasa et al [41], Alzoubi [39], Mohanty and Krishnankutty [33] also confirmed the same type of findings.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Among these variables, Equity to Asset Ratio (EAR) and Deposit to Asset ratio (DTAR) are statistically significant [30,31] at 1% level of significance on ROA-and have significant impact of GDPGR-Gross Domestic Product Growth Rate on ROA-Return on Asset at 5% level of significance. Several researchers [8,12,15] found same type of findings. Tan and Floros [36], Ariyadasa et al [41], Alzoubi [39], Mohanty and Krishnankutty [33] also confirmed the same type of findings.…”
Section: Discussionsupporting
confidence: 58%
“…), mobile banking, ATM service, SME banking, SMS banking, internet banking, credit card, foreign currency account, locker service are the services of banking sector in Bangladesh [7]. Corporate banking, real-time online banking for corporate clients, loan syndication are also the services of banking sector in Bangladesh [8]. Since many years have passed and till now banking sector plays the most significant role for the country's development, hence it is important to evaluate the performance of the banking sector [2].…”
Section: Introductionmentioning
confidence: 99%
“…Kajian kualitas pelayanan terhadap kepuasan dapat dilihat dari beberapa sektor. Pertama, di sektor perbankan kajian dilakukan oleh (Alamgir Hossain, Yesmin, Jahan, & Kim, 2021;Aslam, Tariq, & Arif, 2019;Fauzi & Suryani, 2019;Islam, Ahmed, Rahman, & Asheq, 2020;Rahaman, Ali, Kejing, Taru, & Mamoon, 2020;Wiyanto, 2016). Kedua, di sektor teknologi kajian dilakukan oleh (Pawirosumarto, 2016;Setiawan, 2016).…”
Section: A Pendahuluanunclassified
“…Kualitas pelayanan merupakan tingkat perbedaan antara harapan dan presepsi serta penilaian atau sikap konsumen secara elaboratif terhadap kinerja layanan yang sedang dirasakan (Islam et al, 2020;Kang, 2020). Kualitas pelayanan merupakan faktor penting bagi organisasi atau perusahaan dalam meningkatkan daya saing, perkembangan dan pertumbuhan bisnis (Rahaman et al, 2020). Kemudian kualitas pelayanan juga merupakan faktor penting dalam menafsirkan kepuasan (Balinado et al, 2021) Dimensi kualitas pelayanan terdiri dari (Alam, 2021;Balinado et al, 2021;Fauzi & Suryani, 2019): (a) Reliability (kehandalan), kemampuan untuk memberikan pelayanan yang sesuai dengan tawaran.…”
Section: B Kajian Pustakaunclassified
“…Competition is increasing day by day. The banking sector needs to be dynamic with continuous development in a highly competitive environment (Rahaman et al, 2020). Sixty-one scheduled banks in Bangladesh are functioning very efficaciously.…”
Section: Introductionmentioning
confidence: 99%